A Part-Of-Speech Tagging Approach for Chinese-Hmong Mixed Text. Issue 1 (May 2020) - Li, Hang-Cheng; Mo, Li-Ping; Qing Zhou, Kai
Abstract: Part-of-speech (POS) tagging is a basic problem that needs to be solved in the informationization of Chinese-Hmong mixed text including square Hmong characters, so far no one has studied it. This paper proposes a POS tagging approach for Chinese-Hmong mixed text by utilizing improved Hidden Markov Model (HMM) to expand contextual information. The results of comparative experiments based on cross-validation reveal the proposed approach has perfect performance, and is able to obtain tagging results with good consistency and high coverage.